Blink the power of thinking without thinking - Gladwell, Malcolm 1963- (New York Little, Brown and Company, 2005)
How do we think without thinking, seem to make choices in an instant--in the blink of an eye--that actually aren't as simple as they seem? Why are some people brilliant decision makers, while others are consistently inept? Why do some people follow their instincts and win, while others end up stumbling into error? And why are the best decisions often those that are impossible to explain to others? Drawing on cutting-edge neuroscience and psychology, the author reveals that great decision makers aren't those who process the most information or spend the most time deliberating, but those who have perfected the art of filtering the very few factors that matter from an overwhelming number of variables.
The statue that didn't look right -- The theory of thin slices : how a little bit of knowledge goes a long way -- The locked door : the secret life of snap decisions -- The Warren Harding error : why we fall for tall, dark, and handsome men -- Paul Van Riper's big victory : creating structure for spontaneity -- Kenna's dilemma : the right-and wrong-way to ask people what they want -- Seven seconds in the Bronx : the delicate art of mind-reading -- Conclusion : listening with your eyes : the lessons of blink.
Includes bibliographical references (pages [255]-262) and index.
Keywords: Decision making; Intuition